2020
DOI: 10.1186/s12891-020-03557-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patient satisfaction after operative and nonoperative treatment for midshaft clavicle fractures: a focus group analysis

Abstract: Background: There is no consensus on the optimal treatment for displaced midshaft clavicle fractures. Several studies indicate superior patient satisfaction in favour of operative reconstruction. It is unknown what drives superior satisfaction in this treatment group. The aim of this study was to explore patient satisfaction and identify contributors to patient satisfaction after operative and nonoperative treatment for displaced midshaft clavicle fractures in adults using a focus group approach. Methods: Four… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This is in line with findings from previous studies, where lack of information was the major cause of dissatisfaction. 18,28 A study by Longstaffe et al in 2015 showed that surgeons and physiotherapists reported a negative view of their interprofessional communication. 29 Both surgeons and physiotherapists in this study did often disagree on information provided to patients concerning several aspects of rehabilitation, such as the aim of treatment and referral criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with findings from previous studies, where lack of information was the major cause of dissatisfaction. 18,28 A study by Longstaffe et al in 2015 showed that surgeons and physiotherapists reported a negative view of their interprofessional communication. 29 Both surgeons and physiotherapists in this study did often disagree on information provided to patients concerning several aspects of rehabilitation, such as the aim of treatment and referral criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The focus group script, which was made by an experienced team of researchers and medical specialists consisting of shoulder dedicated trauma and orthopedic surgeons, was based on the script previously used in a clavicular fracture population (Table 1). 17,18 The first part of the script consisted of four open questions regarding the impact of shoulder instability on daily activities, expectations prior to treatment, up-and downsides during the course of the treatment. Patients were able to freely discuss these subjects within the focus group.…”
Section: Focus Groups and Scriptmentioning
confidence: 99%
“…The collected data were analyzed, processed and saved with the help of statistical package for social sciences (SPSS 21) from which descriptive analysis (percentage, proportions and measures of central tendency) t-test and ANOVA had been used appropriately. Age was categorized into adolescence (13)(14)(15)(16)(17)(18)(19), young adult (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), middle age (36-60) and elder (above 60), Level of pain was categorized into no pain (0), mild pain (1-3), moderate pain (4-6) and severe pain (7-10) and level of perceived satisfaction was categorized into very satisfied, moderately satisfied, moderately dissatisfied and very dissatisfied and scored 3,2,1,0 for the ease of analysis. Marital status was classified as unmarried, married and others.…”
Section: Data Analysis and Processingmentioning
confidence: 99%
“…Widow, widower, divorced, separated and living together were included in category "others". For the ease of reporting overall satisfaction was categorized into very satisfied (26)(27)(28)(29)(30)(31)(32)(33) The participants of our research were given a clear explanation about the details of the research.…”
Section: Data Analysis and Processingmentioning
confidence: 99%
“…Widow, widower, divorced, separated and living together were included in category "others". For the ease of reporting overall satisfaction was categorized into very satisfied (26)(27)(28)(29)(30)(31)(32)(33), moderately satisfied (17)(18)(19)(20)(21)(22)(23)(24)(25), moderately dissatisfied (8)(9)(10)(11)(12)(13)(14)(15)(16) and very dissatisfied (0-7) The participants of our research were given a clear explanation about the details of the research.…”
Section: Data Analysis and Processingmentioning
confidence: 99%